Visions of community in Nazi Germany : social engineering and private lives - Steber, Martina 1976- HerausgeberIn; Gotto, Bernhard 1973- HerausgeberIn (Oxford University Press, 2014)
When the Nazis seized power in Germany in 1933 they promised to create a new, harmonious society under the leadership of the Fuhrer, Adolf Hitler. The concept of volksgemeinschaft - the people's community - enshrined the Nazis' vision of society; a society based on racist, social-Darwinist, anti-democratic, and nationalist thought. This book scrutinizes volksgemeinschaft as the Nazis' central vision of community